Unraveling the effect of differential leadership on employee performance: Evidence from China - Liu, Ning; Zhang, Honglie; Zhou, Jiang (Frontiers in Psychology, 2023)
This paper examines how differential leadership influences employee performance via perceived organizational support and individual-organizational fit. The psychological contract theory investigated how differential leadership influences the performance of employees. The information was obtained by means of surveys distributed to various types of Chinese firms. A total of 358 complete responses for statistical analysis had been received and examined. A structural equation model was used, which we believed would be the most appropriate model for testing the proposed study model. The evidence suggests that differentiated leadership promotes employee performance. The association between leadership differences and employee performance is positively mediated by perceived organizational support. Individual-organizational fit lowers the positive effect of differential leadership on employee performance and reduces the positive effect of organizational support perception on employee performance. The results of this research contribute to a better understanding of Chinese culture's differentiated interpersonal cordial leadership construct.